Peran Badan Narkotika Nasional Provinsi Nusa Tenggara Timur dalam Penegakan Hukum terhadap Tindak Pidana Nartkotika - Susana Amos Pah; Aksi Sinurat; Daud Dima Tallo (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
The circulation of narcotics in Indonesia shows a trend that continues to increase and is very worrying. Currently, narcotics are not only distributed in big cities but have also reached East Nusa Tenggara. This is a dangerous threat to the lives of the community, nation and state, specifically to the survival and future of the perpetrators. The East Nusa Tenggara government has shown its seriousness in eradicating and preventing narcotics abuse by establishing the East Nusa Tenggara Provincial National Narcotics Agency (BNNP). The research method used is qualitative descriptive research, namely to provide a complete picture of the role of the NTT BNNP in carrying out its duties and functions in law enforcement against narcotics crimes and then describe the obstacles faced in eradicating narcotics crimes, both juridically and empirically. This research was carried out at the East Nusa Tenggara Province Narcotics Agency Office. The results of the research conducted show: (1) The role that must be carried out by the NTT Province BNN is a hard power approach through eradication, a soft power approach through prevention, community empowerment and rehabilitation, then a smart power approach using sophisticated information technology as ordered by the president for digitalization. (2) Obstacles encountered by the NTT Province BNN in preventing narcotics abuse include: Human resources are one of the obstacles for the NTT Province BNN in carrying out its role in eradicating narcotics cases in society. Budget is the thing that is most needed in executing an activity and other things. Budget limitations are one of the obstacles for the NTT Province BNN in carrying out its role in eradicating narcotics cases in society. The existing facilities and infrastructure apparently have an impact in hampering the role of the NTT BNNP. Based on this, it can be concluded that in eradicating and preventing narcotics abuse, the NTT BNNP has a role and faces obstacles in doing so.